G575(P) Quality improvement for expediting patient flow by careful removal of a bottle-neck process. (27th April 2016) - Nassir, S; Jyothish, D; Newton, T; Morris, H
Abstract : Context: Birmingham Children's Hospital has one of the busiest ED departments in the country. Children presenting to ED are initially seen by the ED team and if an admission is required, they are referred to the Resident Medical Officer (RMO) who reviews the patient, requests a bed and troubleshoots any issues before going onto the wards. Problem: In the winter, majority of these admissions are infants with bronchiolitis who either need help with their feeding or have an oxygen requirement. With high number of admissions, the sole RMO can have a bottleneck effect on the whole ED department such as delayed movement to the wards and hence delayed waiting times. Assessment of problem and analysis of its causes: In a focus group of RMOs it was established that in majority of these admissions, the RMO merely does a bed request as the standards of care, from our bronchiolitis pathway, are already put in place by the initial ED clinician. Hence, these patients are waiting for the RMO with no extra clinical input. This causes unnecessary delays in busy times. Intervention: A stakeholders meeting was organised with a focus on improving this issue. A new strategy of direct hospital admissions of typical bronchiolitis patients that bypasses the RMO was devised and analysed thoroughly. Hospital risk assessment team helped in evaluating the risks of any deviation from the current process. Study design: The 'Focus-Analyse-Develop-Execute' (FADE) cycle approach was used in this Quality Improvement project. The normalisation process theory helped in avoiding duplication and providing right treatment for the patients without delay. Strategy for change: The implementation of this Quality improvement change is scheduled for early December where a typical bronchiolitis child who needs admission for feeding support or oxygen requirement and is classed as moderate on the bronchiolitis pathway, will bypass the RMO once a senior ED clinician has advised admission. Patients classified as severe bronchiolitis will need RMO review before admission. RMO will also review patients that have concerns raised from any member of the ED team despite being in the moderate category. Dedicated members of the ED and General Paediatrics team are given the task to informing their respective departmental staff of this change. A hospital teaching session was done before starting the project. Emails will be generated explaining this change to the respective staff. Measurement of improvement: We are currently in the stage of execution and are hoping to see the positive effects of this change on patient experience and improved ED patient flow. Effects of changes: Analysis will be done in time to assess definitive decision making, time of bed request and transfer to the ward. We are hoping to see the positive changes we envisaged such as avoiding duplication, expediting patient flow, and preventing unnecessary delays in admission. Lessons learnt: This process involved a multidisciplinary team and it has brought the departments closer in order to provide optimal care. Openness, support and continuous re-enforcement helped in implementing this change. Message for others: Clear identification and verification of the problem with stakeholders meant everyone engaged from the outset. Trust and confidence with the team members including the risk assessment team helped for the acceptance without much hindrance as safety was ensured. The main task of this project was to improve the productivity of the manpower on the frontline of the hospital and so ultimately increasing the value of care to patients.